Las ecuaciones diferenciales de los procesos de nacimiento y muerte y el problema de momentos de Stieltjes (2017)
"The objective of the following thesis is to understand how the theory of orthogonal polynomials and the Stieltjes moment problem can be used to study stochastic processes. The principal source for this work is a series of articles written by S. Karlin and J. L. McGregor. In these articles, the strong relation between the previously mentioned theories is established. An introduction to the theory of stochastic processes will be made followed by the corresponding introduction tp the theory of orthogonal polynomials. Finally, the relation between this theories will be established and an application of this fact to the solution of forward and backward equations will be discussed." -- Tomado del Formato de Documento de Grado.